Amy will pay $3.00 for the tiles for her bathroom floor.
A fraction represents a part of a whole.
The scale is 1/2 inch = 1 foot.
Length of bathroom = 3 inches × (1 foot / 24 inches)
= 1/8 feet
Width of bathroom = inches(1 foot / 24 inches)
= 7/24 feet
We need to calculate the total area of the bathroom floor in square feet:
Area of bathroom floor = (length) x (width)
= (1/8 feet) x (7/24 feet)
= 7/192 square feet
Since each tile measures 1/2 foot on each side, the area of each tile is:
Area of one tile = (1/2 feet) x (1/2 feet) = 1/4 square feet
Total area of tiles needed = (area of bathroom floor) / (area of one tile)
= (7/192 square feet) / (1/4 square feet)
= 7/48 tiles
Amy will need to purchase 1 tile at a cost of $3.00 per tile, so the total cost of the tiles for her bathroom floor will be:
Total cost = (number of tiles) x (cost per tile)
= 1 tile x $3.00/tile = $3.00
Hence, Amy will pay $3.00 for the tiles for her bathroom floor.
To learn more on Fractions click:
#SPJ3
Answer:
$78.00
Step-by-step explanation:
First, you would have to figure out how many tiles she would need. 3 inches is equal to 6 feet according to the scale part, and then it would be 12 tiles because it is half a foot for the tiles. Then 3 1/2 would be 7 feet, and then 14 tiles. 12 plus 14 equals 26, and 26 times $3.00 is $78.00
7x, because 12x − 8x + 3 = 4x + 3 = 7x
12x − 5, because 12x − (8x − 3) = 12x − 5
x, because 12x − 8x + 3 = 12x − 11x = x
Answer:
A. 3 + 4x, because (12x − 8x) + 3 = 4x + 3 = 3 + 4x.
Step-by-step explanation:
12x − 8x + 3 is equal to 3 + 4x.
1. Make a factor tree( always helps for me).
2. Identify the common numbers that make it.
3. 36 and 54 have factors of 2 and 3s in common.
4. Multiply the common factors to find the GCF.
I hope this helped!:)
6.) 3x + By= -1;(2, 7)
Help!! Please
Answer:
5) A = 4
6) B = -1
Step-by-step explanation:
Question 5
Substitute (2, -5) into the equation to find the missing coefficient
A(2) + (-5) = 3
2A - 5 = 3
2A = 8
A = 4
Question 6
Substitute (2, 7) into the equation to find the missing coefficient
3(2) + B(7) = -1
6 + 7B = -1
7B = -7
B = -1